P72 Provision of, and access to, sexual and reproductive health services during Covid-19: qualitative research with staff and clients/patients in England. (26th August 2022) - Aicken, Catherine; Sawyer, Alexandra; Huber, Joerg; Edelman, Natalie; Vera, Jaime; Tanner, Eleanor; Williams, Debbie; Sheta, Alison; McBride, Kerry; McInnes-Dean, Amelia; Lohr, Patricia A; Mirandola, Massimo; et al.
Abstract : Background: The Covid-19 pandemic put unprecedented pressure on health services, including sexual and reproductive healthcare (SRH). Timely access to SRH prevents poor outcomes for individuals, and for population health. To inform future pandemic preparedness, we explored experiences of providing and accessing SRH services in England (within a multi-country, WHO-funded study). Methods: In-depth interviews with a purposive sample of staff (about Covid-19's impact on staff and services) and clients aged 18+ (about experiences of seeking/receiving care) of three contrasting SRH services in southeast England: a sexual health clinic, an abortion provider, and a sexual assault referral centre (SARC). Descriptive Thematic Analysis. Results: Staff (n=8) interviews consistently revealed three themes: (i) Service disruption: severe disruption occurred during the March-July 2020 lockdown, but where feasible SRH services were transferred to telephone (e.g. consultations) and post (e.g. some contraceptive methods, medical abortion, STI self-sampling). Some core services (e.g. STI treatment, SARC services) continued in person. Access was widened during subsequent lockdowns. (ii) Staff impact: staff reported working from home, or providing services in person often with shortages of protective equipment, or redeployment to acute hospital care. Impacts included stress, loneliness, and (for redeployees) mismatches between skill-sets and new responsibilities. (iii) Adjustment and resilience: staff reported continual adjustment in mode of service delivery and breadth of services provided. Remote service delivery was generally welcomed, but considered more time-consuming to deliver. Colleagues' absences were burdensome and stressful for staff. Provisional themes from clients (n=10, recruitment ongoing) include: (i) Perceptions of services as Covid-safe: despite reporting varying concerns about Covid-19's severity and personal vulnerability. (ii) Navigating new routes to care: whilst some clients reported being able to access care rapidly and easily, services delivered in person were not always promptly available, which could be distressing. Discussion: Prompt access to SRH could not always be maintained, despite efforts by staff/services. Remote delivery of some elements of SRH is popular with staff and clients. Staff concerns contrast with clients' perceptions of SRH services as Covid-safe. People who did not use SRH – for whom perceived risk of Covid-19 may have been a barrier to seeking care – should be included in future research. When services were under particular pressure due to staff shortages, referral for client interviews slowed. Experiences of seeking/receiving care at these especially challenging times may therefore be under-explored. Interviews repeated later in 2022 will capture change over time. A quantitative Health Facility Assessment will complement our qualitative findings.